Analisis Kinerja Keuangan Berdasarkan Rasio Likuiditas Dan Profitabilitas Pada PT. MAYORA INDAH Tbk. Periode 2020-2023 - Doloksaribu, Gabriella Evelin Marlina; Silaban, Adanan; Sinurat, Mangasa (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The purpose of this study was to measure and analyze financial performance based on liquidity ratios and profitability ratios at PT Mayora Indah Tbk for the 2020-2023 period. This research uses quantitative descriptive research methods using data from the audited and released financial statements of PT Mayora Indah Tbk from the Indonesia Stock Exchange (IDX). The results of this study indicate that using the liquidity ratio consisting of current ratio, quick ratio and cash ratio achieved by the company during the four periods from 2020 to 2023 has fluctuated, but the company's liquidity level is still good because it is still above the industry average standard which shows that the company uses assets owned by the company to meet its short-term obligations. And using profitability ratios consisting of return on assets, return on equity, return on investment, gross profit margin, and net profit margin in 2020 to 2021 has decreased and in 2022 to 2023 the company has increased but is still far below the average standard industry ratio so that it shows that the company's profitability is not good. Thus, it can be concluded that liquidity has a close relationship with profitability, this indicates a large placement of funds on the current asset side. Suggestions that can be useful for company management are to improve the financial performance of PT Mayora Indah Tbk, management should utilize existing capital more effectively through profitable investments, such as product development, in order to increase sales and expand market share.For future researchers, it is recommended that further research be carried out with a longer period of time.In addition, the ratio used is added again in measuring financial performance, so that the results obtained are maximized.